STUDY OF THE PRACTICAL SIGNIFICANCE OF BENZIMIDAZOLE AND SOME OF ITS DERIVATIVES (ResearchJet Journal of Analysis and Inventions, 2023)
Biologically active compounds and their derivatives have been the basis for many studies and are of great practical importance due to their versatile biological activities, including antifertility, antiviral, anticancer, antioxidant, antitrypanosomal, antimicrobial and antimalarial activities. The article explains the practical importance of one such compound - benzimidazole and some of its derivatives.